Demographic history of speciation in a Senecio altitudinal hybrid zone on Mt. Etna. - Filatov, D; Osborne, O; Papadopulos, A (Wiley, 2016)
Hybrid zones typically form as a result of species coming into secondary contact, but can also be established in situ as an ecotonal hybrid zone, a situation which has been reported far less frequently. An altitudinal hybrid zone on Mount Etna between two ragwort species (the low elevation Senecio chrysanthemifolius and high elevation S. aethnensis) could potentially represent either of these possibilities. However, a scenario of secondary contact vs. speciation with gene flow has not been explicitly tested. Here, we test these alternatives and demonstrate that the data do not support secondary contact. Furthermore, we report that the previous analyses of speciation history of these species were based on admixed populations, which has led to inflated estimates of ongoing, interspecific gene flow. Our new analyses, based on 'pure' S. aethnensis and S. chrysanthemifolius populations, reveal gene exchange of less than one effective migrant per generation, a level low enough to allow the species to accumulate neutral, genomewide differences. Overall, our results are consistent with a scenario of speciation with gene flow and a divergence time which coincides with the rise of Mt. Etna to altitudes above 2000 m (~150 KY). Further work to quantify the role of adaptation to contrasting environments of high and low altitudes will be needed to support the scenario of recent ecological speciation in this system.